Communication and society - "Mahajan, Kamlesh (ed.)" (New Delhi, 1990)
The human society is undergoing the tremors of a communication revolution. The flood of information has opened new vistas of generation and dissemination of ideas. Natu rally, the social scientists are attracted and agitated by the phenomenon of mass com munication. The book is devoted to the discussion of various conceptual, methodo logical and substantial issues related to the interaction between mass communication and the social system. The papers, written by the acknowledged scholars in the field of mass media and mass communication, reflect inte resting issues like the role of communication in development, impact of television on society and its role in the process of moderni zation, communication and its impact on utilization of leisure and the formulation of cultural policy, the sociological approach to communication, and applied aspects of mass communication in relation to women's deve lopment, urbanization, modernization and political behaviour. Some innovative media like cartoons, toys and terminals, their uses and limitations in the process of mass com munication have also been looked into.
Keywords: Communication